Return to sport after nonoperative management of elbow ulnar collateral ligament injuries: A systematic review and meta-analysis - Gopinatth, V.; Batra, A. K.; Zeeshan A. K.; Jackson, G. R.; Jawanda, H. S.; Mameri, E. S.; McCormick, J. R.; Knapik, D. M.; Chahla, J.; Verma, N. N. (The American Journal of Sports Medicine, 2023)
Background: Elbow ulnar collateral ligament (UCL) injuries can result in significant functional impairment in throwing and overhead athletes. UCL reconstruction and repair are proven treatments to restore stability, but the efficacy of nonoperative management is unclear.